2017
DOI: 10.1007/s11192-017-2438-3
|View full text |Cite
|
Sign up to set email alerts
|

Online distribution channel increases article usage on Mendeley: a randomized controlled trial

Abstract: Prior research shows that article reader counts (i.e. saves) on the online reference manager, Mendeley, correlate to future citations. There are currently no evidenced-based distribution strategies that have been shown to increase article saves on Mendeley. We conducted a 4-week randomized controlled trial to examine how promotion of article links in a novel online cross-publisher distribution channel (TrendMD) affect article saves on Mendeley. Four hundred articles published in the Journal of Medical Internet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…The social reference sharing site Mendeley (Henning & Reichelt, 2008) provides a convenient source of readership data (e.g., Kudlow, Cockerill, Toccalino, Dziadyk, Rutledge, Shachak, & Eysenbach, 2017;Zahedi, & van Eck, 2018) from the minority of researchers that use it (Van Noorden, 2014). Many studies have shown that Mendeley readership counts positively correlate with counts of citations to published journal articles (e.g., Costas, Zahedi, & Wouters, 2015;Thelwall, Haustein, Larivière, & Sugimoto, 2013;Zahedi, Costas, & Wouters, 2014).…”
Section: Mendeley Readership Countsmentioning
confidence: 99%
“…The social reference sharing site Mendeley (Henning & Reichelt, 2008) provides a convenient source of readership data (e.g., Kudlow, Cockerill, Toccalino, Dziadyk, Rutledge, Shachak, & Eysenbach, 2017;Zahedi, & van Eck, 2018) from the minority of researchers that use it (Van Noorden, 2014). Many studies have shown that Mendeley readership counts positively correlate with counts of citations to published journal articles (e.g., Costas, Zahedi, & Wouters, 2015;Thelwall, Haustein, Larivière, & Sugimoto, 2013;Zahedi, Costas, & Wouters, 2014).…”
Section: Mendeley Readership Countsmentioning
confidence: 99%
“…High correlations between Mendeley reader counts and citation counts in almost all narrow fields (n = 325) suggest that readership data is a type of scholarly impact indicator (Thelwall 2017). It is particularly useful as a source of early impact evidence (Kudlow et al 2017). Mendeley asks users to register some information about themselves, such as their occupation, country and subject area.…”
Section: Introductionmentioning
confidence: 99%
“…This research indicated many Mendeley users are importing papers from the existing library. Various popular reference management tools exist to help researchers increase research and publication trend [17]. Furthermore, this research also showed many Mendeley users were rather qualified to import papers either from desktop or website.…”
Section: P8mentioning
confidence: 77%